EVALUASI PROGRAM PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DI KELURAHAN SARIREJO KECAMATAN SEMARANG TIMUR KOTA SEMARANG - Dewi Ratna Siti Mukaromah; Dewi Rostyaningsih (Journal of Public Policy and Management Review, 2016)
Based on the records of PHBS from 2012 to 2014 there is a decline of PHBS program implementation in Sarirejo Village Eastern Semarang, Semarang City. This indicates a problem that can be researched to find out the cause. The purpose of this research is to evaluate and to find the cause of problem in the implementation of the Perilaku Hidup Bersih dan Sehat (PHBS) Program. This method is a qualitative research and is a descriptive type. Snowball sampling is used to find the informants for this research. . Data gathering techniques used in this research are observation, interviews, literature, and documentation. The response of the PHBS Program from the public is insufficient. The PHBS program was not able to reach all the targeted groups. Only one targeted group was reached, the elderly group. Based on the research can be conclusion is responsiveness of the PHBS Program was not to reach of the targeted groups. Core issue of the PHBS Program is lack of advocacy and social support from government, low level of knowledge and public awareness. The recommendation for government to make a figure, commitment, and have a good relationship with society. As well as, for society to leave unhealthy behaviors with to increase of knowledge and healty awareness.